2017
DOI: 10.1021/acs.jmedchem.7b00631
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Potent and Specific M. tuberculosis Leucyl-tRNA Synthetase Inhibitor: (S)-3-(Aminomethyl)-4-chloro-7-(2-hydroxyethoxy)benzo[c][1,2]oxaborol-1(3H)-ol (GSK656)

Abstract: There is an urgent need to develop new and safer antitubercular agents that possess a novel mode of action. We synthesized and evaluated a novel series of 3-aminomethyl 4-halogen benzoxaboroles as Mycobacterium tuberculosis (Mtb) leucyl-tRNA synthetase (LeuRS) inhibitors. A number of Mtb LeuRS inhibitors were identified that demonstrated good antitubercular activity with high selectivity over human mitochondrial and cytoplasmic LeuRS. Further evaluation of these Mtb LeuRS inhibitors by in vivo pharmacokinetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
106
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(108 citation statements)
references
References 27 publications
(52 reference statements)
1
106
0
1
Order By: Relevance
“…Besides their antiparasitic effects, ARS inhibitors also played an important role in the antibacterial and antifungal processes [45][46][47][48] . By evaluating the inhibitory effect of a series of 3-aminomethyl 4-halogen benzoxaboroles on Mtb leucyl-tRNA synthetase (LeuRS), Li et al 49 found that one of the compounds, GSK656, was highly selective for Mtb LeuRS and had good antitubercular activity and tolerability in the mid-nanomolar range. Moreover, thiazolin-4-one derivatives as WRS inhibitors showed higher activity against Gram positive bacterial strains than Gram negative bacterial strains 50 .…”
Section: Pathogen Arss Serve As Anti-infective Targetsmentioning
confidence: 99%
“…Besides their antiparasitic effects, ARS inhibitors also played an important role in the antibacterial and antifungal processes [45][46][47][48] . By evaluating the inhibitory effect of a series of 3-aminomethyl 4-halogen benzoxaboroles on Mtb leucyl-tRNA synthetase (LeuRS), Li et al 49 found that one of the compounds, GSK656, was highly selective for Mtb LeuRS and had good antitubercular activity and tolerability in the mid-nanomolar range. Moreover, thiazolin-4-one derivatives as WRS inhibitors showed higher activity against Gram positive bacterial strains than Gram negative bacterial strains 50 .…”
Section: Pathogen Arss Serve As Anti-infective Targetsmentioning
confidence: 99%
“…The aminoacylation assay was performed according to the literature [32,33]. All test compounds were dissolved in CH 3 OH.…”
Section: Aminoacylation Assaymentioning
confidence: 99%
“…18,19 While, there are no commercially approved tRNA synthase inhibitors for the treatment of TB, several inhibitors have been outlined in the literature. [20][21][22][23] Specifically, the 3-aminomethyl compounds containing boron that successfully inhibit mycobacterial leucyl-tRNA synthetase, 21,22 as well as, various inhibitors of aspartyl-tRNA synthetase. 20,23 Drug discovery and target identification is a laborious process that is bottlenecked at several key points.…”
Section: Introductionmentioning
confidence: 99%